(untitled) (Journal of the Sylhet Agricultural University, 2025)
Organic fertilizer production from cattle waste lessens environmental damage and improves the standard of living of cattle farmers through uncovering additional income sources. Majority of the cattle farmers in Bangladesh either are unaware about eco-friendly farming, or they fail to comprehend the potentials of utilizing cattle waste as organic fertilizer. This study aims to determine the socio-economic and farm-level factors that influence the farmers to produce organic fertilizer from cattle waste. From four rural villages in Bogura district of Bangladesh, 84 households who rear cattle were selected randomly, and then interviewed following a well-structured survey schedule. Descriptive statistics and binary logit model were used to analyze the data. It was evident that, 71% of the selected cattle farmers adopted organic fertilizer production. Minimum socioeconomic differences were observed among the cattle rearing households. Six explanatory variables namely education of the household head, farming experience, risk perception, cattle rearing subsidy, access to internet, and farm’s distance from the nearest extension office were found to have significant influence towards farmer’s adoption of organic fertilizer production. For ensuring sustainable adoption, farmers should be made aware regarding green farming through proper on field training and frequent campaigns. In addition, continuous subsidy along with logistic support from both government and non-government organizations must be ensured to encourage the farmers towards organic fertilizer production. J. Sylhet Agril. Univ. 11(2): 81-88, 2024